Orphan Nuclear Receptor NR4A2 Is Constitutively Expressed in Cartilage and Upregulated in Inflamed Synovium From hTNF-Alpha Transgenic Mice - Lilley, Cullen M.; Alarcon, Andrea; Ngo, My-Huyen; Araujo, Jackeline S.; Marrero, Luis; Mix, Kimberlee S. (Frontiers in Pharmacology, 2022)
Orphan nuclear receptor 4A2 (NR4A2 / Nurr1) is a constitutively active transcription factor with potential roles in the onset and progression of inflammatory arthropathies. NR4A2 is overexpressed in synovium and cartilage from individuals with rheumatoid arthritis (RA), psoriatic arthritis, and osteoarthritis. This study documents the expression and tissue localization of NR4A2 and upstream regulator nuclear factor kappa B (NF-KB) in the human tumor necrosis factor-alpha (hTNF-a) transgenic mouse model of RA. Since TNF-a is a potent inducer of NR4A2 in vitro, we hypothesized that NR4A2 would also be upregulated and active during disease progression in this model. Expression levels of NR4A2, related receptors NR4A1 (Nur77) and 3 (NOR1), and NF-KB1 transcripts were quantified by RT-qPCR in hTNF-a and wild-type joints at three stages of disease. The protein distribution of NR4A2 and NF-KB subunit RelA (p65) was analyzed by quantitative immunohistochemistry. Global gene expression of 88 RA-related genes was also screened and compared between groups. Consistent with previous reports on the hTNF-a model, transgenic mice exhibited significant weight loss and severely swollen paws by 19 weeks of age compared to age-matched wild-type controls. NR4A1-3 and NF-KB1 were constitutively expressed at disease onset and in healthy joints. NF-KB1 transcript levels increased 2-fold in hTNF-a paws with established disease (12 weeks), followed by a 2-fold increase in NR4A2 at the late disease stage (19 weeks). NR4A2 and RelA proteins were overexpressed in inflamed synovium prior to symptoms of arthritis, suggesting that gene expression changes documented in whole paws were largely driven by elevated expression in diseased synovium. Broader screening of RA-related genes by RT-qPCR identified several differentially expressed genes in hTNF-a joints including those encoding inflammatory cytokines and chemokines, matrix-degrading enzymes and inhibitors, cell surface receptors, intracellular signaling proteins and transcription factors. Consensus binding sites for NR4A receptors and NF-KB1 were enriched in the promoters of differentially expressed genes suggesting central roles for these transcription factors in this model. This study is the first comprehensive analysis of NR4A2 in an animal model of RA and validates the hTNF-a model for testing of small molecules and genetic strategies targeting this transcription factor.